Blog theory feedback and capture in the circuits of drive - Dean, Jodi 1962- (Cambridge, [England] Polity, 2010)
A leading media theorist engages with the world of blogs and social networking sites. Jodi Dean is well known for her work on media theory and what she calls 'communicative capitalism'. The book is a highly original reflection on the way we communicate and think in new media like blogs, Twitter and Facebook.
Blog settings -- The death of blogging -- Whatever blogging -- Affective networks.
Keywords: Blogs -- Social aspects; Blogs -- Political aspects; Online social networks; Social media; Digital media